Acceptability of at-issue co-speech gestures under contrastive focus. Issue 1 (21st January 2019) - Esipova, Maria
Abstract : The status of content-bearing co-speech gestures, i.e., gestural adjuncts co-occurring with the verbal expressions they adjoin to, has recently become a matter of debate in formal semantics and pragmatics (Ebert & Ebert 2014 ; Ebert 2017 ; Tieu et al. 2017 ; 2018; Esipova 2018 ; Schlenker 2018 ; Zlogar & Davidson 2018 ). The general tendency has been to claim that co-speech gestures by default make not-at-issue contributions, however, the existing analyses differ in whether they in principle allow for at-issue interpretations of co-speech gestures and, if yes, in how much cost such at-issue interpretations can incur. In this study I use an acceptability judgement task to investigate the acceptability of at-issue interpretations of co-speech gestures forced by contrastive focus, as well as some factors that can potentially affect that acceptability. I conclude that while the overall results are in principle compatible with any analysis that posits a (strong) bias against at-issue interpretations of co-speech gestures, further inspection of individual variation in judgement patterns allows us to argue against analyses in which the level of such bias is fixed across speakers. In particular, the variation data can be taken as evidence against the analysis of co-speech gestures as Pottsian (2005 ) supplements akin to appositives (Ebert & Ebert 2014 ; Ebert 2017 ). As for the factors that can potentially affect the acceptability of at-issue interpretations of co-speech gestures under contrastive focus, neither the type of content encoded by the gesture, nor emphatic production of co-speech gestures have been found to have an effect.